Alpha-lipoic acid supplementation restores the meiotic competency and fertilization capacity of porcine oocytes induced by arsenite - Zhang, Mianqun; Sun, Lei; Zhang, Zihao; Shentu, Luyan; Zhang, Yiwen; Li, Ziyi; Zhang, Yongteng; Zhang, Yunhai (Frontiers in Cell and Developmental Biology, 2022)
Arsenite is known as a well-known endocrine disrupting chemicals, and reported to be associated with an increased incidence of negative health effects, including reproductive disorders and dysfunction of the endocrine system. However, the influence of arsenite on the oocyte quality and the strategy to prevent it has not yet fully determined. Here, we report that supplementation of alpha-lipoic acid (ALA), a strong antioxidant naturally present in all cells of the humans, is able to restore the declined meiotic competency and fertilization capacity of porcine oocytes induced by arsenite. Notably, ALA recovers the defective nuclear and cytoplasmic maturation of porcine oocytes caused by arsenite exposure,,including the impaired spindle formation and actin polymerization, the defective mitochondrion integrity and cortical granules distribution. Also, ALA recovers the compromised sperm binding ability to maintain the fertilization potential of arsenite-exposed oocytes. Importantly, ALA suppresses the oxidative stress by reducing the levels of ROS and inhibits the occurrence of DNA damage along with apoptosis. Above all, we provide a new perspective for the application of ALA in effectively preventing the declined oocyte quality induced by environmental EDCs.